2019
DOI: 10.1111/1462-2920.14511
|View full text |Cite
|
Sign up to set email alerts
|

Sharing cells with Wolbachia: the transovarian vertical transmission of Culex pipiens densovirus

Abstract: Summary Culex pipiens densovirus (CpDV), a single stranded DNA virus, has been isolated from Culex pipiens mosquitoes but differs from other mosquito densoviruses in terms of genome structure and sequence identity. Its transmission from host to host, the nature of its interactions with both its host and host's endosymbiotic bacteria Wolbachia are not known. Here, we report the presence of CpDV in the ovaries and eggs of Cx. pipiens mosquitoes in close encounters with Wolbachia. In the ovaries, CpDV amount sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 67 publications
(101 reference statements)
3
36
0
Order By: Relevance
“…First, many commensal bacteria may not always stop pathogen development in the mosquito. For example, Serratia inhibits malaria parasite infection of mosquitoes (Gonzalez-Ceron et al, 2003;Bando et al, 2013;Wang et al, 2017), while it promotes dengue virus infection of a culicine mosquito (Wu et al, 2019); A Wolbachia species reduces arbovirus infection of A. aegypti mosquitoes (Moreira et al, 2009;van den Hurk et al, 2012;Dutra et al, 2016) whereas another species enhances vertical densovirus transmission by Culex pipiens (Altinli et al, 2018;King et al, 2018). These apparently contradictory observations will only be clarified when the mechanisms underlying the observed effects are understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, many commensal bacteria may not always stop pathogen development in the mosquito. For example, Serratia inhibits malaria parasite infection of mosquitoes (Gonzalez-Ceron et al, 2003;Bando et al, 2013;Wang et al, 2017), while it promotes dengue virus infection of a culicine mosquito (Wu et al, 2019); A Wolbachia species reduces arbovirus infection of A. aegypti mosquitoes (Moreira et al, 2009;van den Hurk et al, 2012;Dutra et al, 2016) whereas another species enhances vertical densovirus transmission by Culex pipiens (Altinli et al, 2018;King et al, 2018). These apparently contradictory observations will only be clarified when the mechanisms underlying the observed effects are understood.…”
Section: Discussionmentioning
confidence: 99%
“…Infection by the wMel strain of Wolbachia also can significantly reduce CHIKV and Yellow Fever virus (YFV) infection and dissemination rate (van den Hurk et al, 2012). However, a Wolbachia strain was reported to enhance vertical densovirus transmission by Culex pipiens (Altinli et al, 2018;King et al, 2018).…”
Section: Impact Of Microbiota On Mosquito Refractoriness To Pathogensmentioning
confidence: 99%
“…Adult mortality has not been evaluated in this work, but many studies have shown that DVs infection of mosquito larvae affects the life traits of infected adults 33 , 34 , 37 . Thus, the effects of sublethal infection of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…pipiens and Culiseta annulata 19 . MDVs are thought to persist in nature by horizontal transmission from larvae to larvae in the wild aquatic environments, although transovarial and sexual transmission have also been recorded 3 , 20 , 27 , 33 37 . They are highly pathogenic for larvae at all stages, but mortality is higher when infection occurs at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although usually applied to animals rather than plants or microbes, this definition of ‘behavior’ encompasses all types of organisms and their populations. Indeed, besides articles on animal hosts (Koehler et al ., ; Murfin et al ., ; Truitt et al ., ; Altinli et al ., ; Rothman et al ., ; Zhao et al ., ), this special issue contains a number of research papers devoted to understanding how plants respond to their microbial inhabitants. Among these studies on plant–symbiont interactions, several focus on plant responses to nitrogen‐fixing bacteria (Lamouche et al ., ; Baena et al ., ; Bañuelos‐Vazquez et al ., ; Pujic et al ., ; Songwattana et al ., ), while others investigate endophytes and their role in alleviating plant abiotic stress (Vigani et al ., ; Lanza et al ., ; Llorens et al ., ).…”
mentioning
confidence: 99%